Theories of experience value & mental health at tourism destinations: Senses, personalities, emotions and memories. (December 2022) - Buckley, R.C.; Cooper, M.A.; Chauvenet, A.; Zhong, L.S.
Abstract: Mental health and experience value at tourism destinations are multidimensional concepts with complex mechanisms. They are built on parallel bodies of research, especially for outdoor nature and adventure destinations. Their theoretical frameworks have the same components, connected in the same structures: place and activity, personalities, senses, emotions, and memories. The two distinct outcomes, health and experience respectively, depend on detailed differences in how these components are perceived and processed by individual tourists at particular destinations. Quantitative measures are already available for tourist personality and satisfaction, but not yet for tourist senses, emotions, memories, or mental health. Since each has multiple components, vector or matrix measures will be needed. We propose these as priorities for future research in destination marketing and management. Graphical abstract: Image 1 Highlights: Theories of tourism experience value and mental health are congruent. Both theories rely on senses, personalities, emotions, and memories. They differ only in the outcome variables, namely satisfaction and health. Mental health research is therefore applicable in destination marketing. Destination experience research is also applicable in therapy design.